Question
upstudy study bank question image url

23) \( \left(\frac{1}{16}\right)^{3 n-3} \cdot 16^{3 n-2}=64^{-n-3} \)

Ask by Bright Watkins. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The solution is \( n = -\frac{11}{3} \) or \( n = -3.6 \).

Solution

Solve the equation \( \left(\frac{1}{16}\right)^{3 n-3} \cdot 16^{3 n-2}=64^{-n-3} \). Solve the equation by following steps: - step0: Solve for \(n\): \(\left(\frac{1}{16}\right)^{3n-3}\times 16^{3n-2}=64^{-n-3}\) - step1: Multiply the terms: \(16=64^{-n-3}\) - step2: Swap the sides: \(64^{-n-3}=16\) - step3: Rewrite in exponential form: \(2^{6\left(-n-3\right)}=2^{4}\) - step4: Set the exponents equal: \(6\left(-n-3\right)=4\) - step5: Divide both sides: \(\frac{6\left(-n-3\right)}{6}=\frac{4}{6}\) - step6: Divide the numbers: \(-n-3=\frac{2}{3}\) - step7: Move the constant to the right side: \(-n=\frac{2}{3}+3\) - step8: Add the numbers: \(-n=\frac{11}{3}\) - step9: Change the signs: \(n=-\frac{11}{3}\) The solution to the equation \( \left(\frac{1}{16}\right)^{3 n-3} \cdot 16^{3 n-2}=64^{-n-3} \) is \( n = -\frac{11}{3} \) or \( n = -3.6 \).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Mind Expander

To solve the equation \( \left(\frac{1}{16}\right)^{3 n-3} \cdot 16^{3 n-2}=64^{-n-3} \), we start by expressing everything in terms of powers of 2. First, note that: \[ 16 = 2^4 \quad \text{and thus} \quad \frac{1}{16} = 2^{-4} \] We can rewrite the left-hand side: \[ \left(\frac{1}{16}\right)^{3 n-3} = (2^{-4})^{3 n-3} = 2^{-4(3n-3)} = 2^{-12n + 12} \] \[ 16^{3 n-2} = (2^4)^{3 n-2} = 2^{4(3n-2)} = 2^{12n - 8} \] Now, multiplying these together: \[ \left(\frac{1}{16}\right)^{3 n-3} \cdot 16^{3 n-2} = 2^{-12n + 12} \cdot 2^{12n - 8} = 2^{-12n + 12 + 12n - 8} = 2^{4} \] Now, for the right-hand side: \[ 64 = 2^6 \quad \text{so} \quad 64^{-n-3} = (2^6)^{-n-3} = 2^{-6(n+3)} = 2^{-6n - 18} \] Now, we set the two sides equal: \[ 2^{4} = 2^{-6n - 18} \] By equating the exponents: \[ 4 = -6n - 18 \] Next, we solve for \( n \): \[ 6n = -18 - 4 \] \[ 6n = -22 \] \[ n = -\frac{22}{6} = -\frac{11}{3} \] Thus, the solution to the equation is: \[ \boxed{-\frac{11}{3}} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy